Functionalization Of Zinc Oxide Nanorods For Glucose Biosensor Application - Ridhuan, Nur Syafinaz (2019)
Electrochemical based glucose biosensors are of interest owing to its simplicity, portable, low cost and does not require specialize personnel. However, this type of biosensors suffers from low sensitivity owing to indirect electron transfer and decrease in long term stability due to enzyme denaturation. Therefore, modification of electrode for electrochemical based glucose biosensors could overcome these problems. Nanostructure electrodes could enhance the performance of glucose biosensors owing to high surface area and biocompatibility with glucose oxidase (GOx) enzyme. In this work, zinc oxide nanorods (ZnO NRs) was successfully synthesized by hydrothermal method on indium tin oxide (ITO) seeded substrates which was further used as electrodes for glucose biosensor. Field emission scanning electron microscope (FESEM) and X-ray diffractometer (XRD) were used to analyze the morphology and structural properties of synthesized ZnO NRs. Homogeneous density and well-aligned of ZnO NRs was obtained when seed films were annealed at 500 °C and hydrothermally grown for 4 hours. The electrochemical properties of modified electrodes were studied by cyclic voltammetry (CV) and amperometric analysis. The parameters influencing the enzyme activity and modified electrodes performance were studied: electrolyte pH, electrolyte temperature, Nafion concentration and GOx enzyme concentration. The modified electrode was designated as Nafion/GOx/ZnONRs/ZnO/ITO. 5 mg/mL of GOx concentration was chosen as the optimum concentration for immobilization on ZnO NRs electrode with high sensitivity of 23.772 μA/mM.cm2. The performance of the prepared electrode when two different immobilization techniques (physical adsorption and cross linking) was employed and compared. ZnO NRs surface was functionalized with glutaraldehyde (cross linking reagent) first before GOx was immobilized and was designated as Nafion/GOx-glutaraldehyde/ZnONRs/ZnO/ITO electrode. Cross-linked GOx electrode showed the best performance with the sensitivity of 32.24 compared to only 23.77 μA/mM.cm2 for physical adsorption GOx electrode. The produced ZnONRs/ITO electrode was also decorated with gold nanoparticles (AuNPs) and platinum nanodendrites (PtNDs). An average diameter of ~40 nm and ~42 nm of AuNPs and PtNDs, respectively, were successfully decorated on ZnO NRs via drop casting method. The sensitivity of Nafion/GOx/ZnONRs/ZnO/ITO, Nafion/GOx/AuNPs/ZnONRs/ZnO/ITO and Nafion/GOx/PtNDs/ZnONRs/ZnO/ITO electrodes was 32.24, 54.51 and 98.34 μA/mM.cm2, respectively. High sensitivity of Nafion/GOx/PtNDs/ZnONRs/ZnO/ITO electrode was due to properties of catalytic properties metallic nanoparticle. With high sensitivity of 98.34 μA/mM.cm2 and low LOD of 0.03 mM Nafion/GOx/PtNDs/ZnONRs/ZnO/ITO electrode was chosen as the best electrode for glucose biosensor. The produced modified electrodes showed excellent performance in human blood samples.